O Ensino de Ciências por meio de Elementos da Cultura Nerd nos Livros Didáticos - Felipe, Thalys (2023)
The following dissertation was elaborated at the Federal University of Uberlândia in the Postgraduate Program in Education, in the Research Line "Science and Mathematics Education" and aimed to investigate the use of Nerd Culture elements in Science schoolbooks of the final years of Elementary School, seeking to understand their representations and didactic purposes.The specific objectives consisted of describing the contents and insertion moments of Nerd culture elements, as well as categorizing and classifying such references according to their representation and function in the didactic materials. Our theoretical background was based on Bauman's consumer culture and from the educational perspective defended by Cortella, which approaches the use of elements from the student's cultural and social universe to facilitate the teaching and learning process. The methodological approach is based on the qualitative study, with the bibliographic investigation as the procedural modality, with the bibliography being the target of our research, four didactic science collections from the final years of elementary school, with the largest number of copies distributed in Brazil. We used Dephth Hermeneutics (DH) to structure the investigation course. The material analysis was initially based on the isolation of all elements of the Nerd culture present in the didactic collections and in due course, the analysis categories were established, in this case, the approaches in which such elements fit: illustrative, contextualized, and reflective approaches. The main study conclusions indicate that Nerd culture elements present in the science books of the final years of elementary school, appear sporadically, being majority characterized within the illustrative approach, serving as a simple illustration for questions and texts. We understand that establishing an analytical look at how such cultural objects are used in science schoolbooks implies considering an approach marked by a playful and superficial bias. Cultural aspects are contemplated essentially in a figurative way and, on rare occasions, they can favor the development of a scientific and reflexive vision of the students. In this movement, thinking about the possibilities and problematizations related to the way in which elements of Nerd culture are used in Science textbooks, favors the debate regarding the use of media products present in the reality of students as potential subsidies for the production of a process thought-provoking and stimulating educational experience for students.